Difficulties and opportunities of implementing total quality management in academic libraries of Ghana - Asante, Edward; Ngulube, Patrick (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Academic libraries are collapsing due to the related challenges of implementing TQM practices and integrating them. Purpose: The primary objective of this study is to ascertain the challenges and prospects of implementing total quality management in Ghanaian university libraries. Method: An explanatory mixed method design was employed in the study. Top management, librarians, faculty members, and administrators took part in the discussion. The information and data were gathered using an interview guide and a questionnaire. Out of the 239 participants, 205 persons provided a valid response. This indicated an 85.7% response rate. Out of the twenty-five individuals who were anticipated, twenty were questioned. For the investigation, a straightforward random and purposive sampling strategy was used. Both quantitative and thematic analysis of the data was done. Findings: The investigation demonstrated that there are difficulties in implementing TQM. Adopting total quality management (TQM) can be difficult due to factors such as staff resistance to change, a lack of facilities and resources, and a lack of commitment from upper management. The study also concluded that implementing TQM has several benefits such as boosting the library system's continual improvement and guaranteeing best practices and standard compliance. Conclusion: The study's conclusions may increase information scientists' and librarians' comprehension of how TQM methods are implemented in Ghanaian academic libraries and experiment with the suggested adoption model.